CULTURAL IDENTITY DEPICTED IN RIRI RIZA’S SOKOLA RIMBA - Pelupessy, Febby Winda; Noya, Natal B.; Wurlianty, Yulandi Ferderika (Prologue: Journal on Language and Literature, 2025)
Abstract: This study aims to analyze how language and identity are related in a film directed by Riri Riza entitled Sokola Rimba. This film follows a struggle of Butet Manurung who teaches Orang Rimba and how she tries to overcome the obstacles. This study applies sociolinguistic frameworks specifically language and identity by John Edwards. The data is divided into three categories namely identity: personal and social, the construction and maintenance of groupness, also language and circumstance. The results of the study show that: (1) all the prominent characters’ identity are shaped by their personal identity as well as the social identity given from the interaction within the social group. (2) The culture and values of Orang Rimba are strongly rooted in their life which enables them to still maintain their group. (3) The use of Kubu language and Bahasa Indonesia symbolize Orang Rimba’s strong culture as well as their willingness to adapt with the changes from outside. It is expected that the future researches can focus on analyzing the use of Kubu language.